Case of peroneus digiti quinti muscle - Chandrika G Teli; H S Kadlimattix (Wolters Kluwer Medknow Publications, 2018)
Lateral compartment muscles of the leg have shown variations like peroneus accessorius, peroneus quartus or peroneus digiti quinti with varied incidences and varied insertions. Here we report a case of peroneus digiti quinti which arose from peroneus brevis tendon and sheath covering it. The small belly moved forwards, diverting from peroneus brevis, midway between peroneus brevis and peroneus tertius, finally inserting on the dorsal digital expansion of fifth toe. Length of muscle belly and tendon were 2.01 cm and 6.5 cm respectively. It was also observed that when traction was applied to peroneus brevis, partial extension of the fifth toe was seen, suggesting functional need to evert and extend the little toe simultaneously.